The protective roles of clusterin in ocular diseases caused by obesity and diabetes mellitus type 2 - de Campos, Thaís Dantis Pereira; da Cruz Rodrigues, Kellen Cristina; Pereira, Rodrigo Martins; Anaruma, Chadi Pellegrini; dos Santos Canciglieri, Raphael; de Melo, Diego Gomes; da Silva, Adelino Sanchez Ramos; Cintra, Dennys Esper; Ropelle, Eduardo Rochete; Pauli, José Rodrigo; de Moura, Leandro Pereira [UNESP] (Springer Nature, 2021)
Obesity is a chronic, non-transmissible and multifactorial disease commonly associated with systemic inflammation and damage to health. This disorder has been pointed out as leading to the development of a diversity of eye diseases and, consequently, damage to visual acuity. More specifically, cardiometabolic risk is associated with lacrimal gland dysfunctions, since it changes the inflammatory profile favoring the development and worsening of dry eye disease. In more severe and extreme cases, obesity, inflammation, and diabetes mellitus type 2 can trigger the total loss of vision. In this scenario, besides its numerous metabolic functions, clusterin, an apolipoprotein, has been described as protective to the ocular surface through the seal mechanism. Thus, the current review aimed to explain the role of clusterin in dry eye disease that can be triggered by obesity and diabetes.
Keywords: Clusterin; Diabetes mellitus; Eye; Lacrimal film; Retina